STUDI PENDAHULUAN PENGEMBANGAN PERANGKAT EKSPERIMEN INDUKSI ELEKTROMAGNETIK ALTERNATIF SEBAGAI MEDIA PEMBELAJARAN FISIKA SMA - Sulvia Nur Oktafiani; Zulirfan Zulirfan; Hendar Sudrajad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This research has various aim among of them, to know the potential of physics learning in electromagnetic induction subject, to identify the constraint of teachers and students in experimental implementation, to look the perception of teachers and students for effective and efficient of experimental equipment and analyzing constraint and perception of students and teachers to design the valid and practice experimental equipment. The research using literature and field study in Research and Development (R&D) method. In collected data through questionnaire and interview, researcher did it for nine of physics teachers and fifty students derive from senior high school in Pekanbaru. Based on document had been analyzed, researcher get conclude ~ applying the electromagnetic induction subject through experimental method is important in physics concept. In fact this method apply rarely, it is impact of any factor like: limited time, limited experimental equipment, full content of the matter and there are no skillful laboratory assistant. In interview teachers and students said the criteria of equipment that they need such as complete, equate real, new, representative, simple, easy to understand, safely, attractive, effective and efficient according to quantity and quality equipment of electromagnetic induction.Key Words: Constraint of physics experiment implementation, electromagnetic induction equipment, physics learning media.